Buy-back policy decision in managing reverse logistics. Issue 3 (11th May 2006) - Mondal, Sandeep; Mukherjee, Kampan
In acquisition planning of Product Recovery Management, the decision maker intends to find out the optimal buy-back period of a used product minimising the economic benefit from remanufacturing. For certain products, which are under a free servicing policy by the company, the acquisition planning is controlled by two indices, one defined by the service management of the company and the other, defined by the working environment at the user's end. In this paper we tried to study this hypothesis and establish the expression of these indices in terms of various economic parameters relating to the remanufacturing process.